2022
DOI: 10.1299/jamdsm.2022jamdsm0050
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of process parameters in laser beam powder bed fusion using surface texture and density of Inconel 718

Abstract: This study aims to optimize the process parameters for PBF-LB of Inconel 718 using the surface texture and density of the as-built specimen to fabricate high-quality products. In order to achieve this aim, the melting and solidification phenomena of the melt pool were examined using a high-speed camera, and the process map of laser power and scan speed was constructed by evaluating the surface texture and density of the as-built specimen to optimize the process parameters. In addition, the mechanical propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…These results may be because of the difference of melting behavior, as stated in Section 2.4. In our previous study [40] and Fig. 3, the surface texture of the process window (regime II) showed evenness due to almost uniform tracks because the melt pool is stable.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…These results may be because of the difference of melting behavior, as stated in Section 2.4. In our previous study [40] and Fig. 3, the surface texture of the process window (regime II) showed evenness due to almost uniform tracks because the melt pool is stable.…”
Section: Resultsmentioning
confidence: 68%
“…Additionally, the authors [40] revealed that the rougher is the surface texture of the solidi ed part, the lower is the density of the manufactured parts and the greater is the number of internal defects. As presented in Fig.…”
Section: Relationship Between Surface Texture Of Powder Bed and Solid...mentioning
confidence: 99%
“…6 The representative melting and solidification behavior observed by high-speed camera at various fabrication conditions. 16) Fig. 4 SEM images of fresh and recycled AlSi10Mg powders (×500).…”
mentioning
confidence: 99%
“…9 The schematic density-based process map between laser power and scan speed including surface texture images. 16) 「粉体および粉末冶金」Advanced Publication by J-STAGE…”
mentioning
confidence: 99%